2019
DOI: 10.1016/j.cophys.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Redox signaling in sickle cell disease

Abstract: Sickle cell disease (SCD) is characterized by chronic hemolysis and repeated episodes of vascular occlusion leading to progressive organ injury. SCD is characterized by unbalanced, simultaneous pro-oxidant and anti-oxidant processes at the molecular, cellular and tissue levels, with the majority of reactions tipped in favor of pro-oxidant pathways. In this brief review we discuss new findings regarding how oxidized hemin, hemolysis, mitochondrial dysfunction and the innate immune system generate oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
1
18
0
3
Order By: Relevance
“…Multiple publications have reported that oxidative stress is elevated in sickle cells, 11,28,29 that this oxidative stress inhibits erythrocyte tyrosine phosphatases, 26,30,31,50 and that inhibition of erythrocyte tyrosine phosphatases leads to elevated tyrosine phosphorylation of Band 3 34,34,35 . We document here that elevated tyrosine phosphorylation of Band 3 causes destabilisation of the membrane, promoting the release of both MPs and cell‐free Hb 34,35,52 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Multiple publications have reported that oxidative stress is elevated in sickle cells, 11,28,29 that this oxidative stress inhibits erythrocyte tyrosine phosphatases, 26,30,31,50 and that inhibition of erythrocyte tyrosine phosphatases leads to elevated tyrosine phosphorylation of Band 3 34,34,35 . We document here that elevated tyrosine phosphorylation of Band 3 causes destabilisation of the membrane, promoting the release of both MPs and cell‐free Hb 34,35,52 .…”
Section: Discussionsupporting
confidence: 54%
“…It has been frequently reported that oxidative stress leads to inactivation of erythrocyte tyrosine phosphatases, 30,31,49 which in turn allow unimpeded tyrosine phosphorylation of Band 3 by constitutively active tyrosine kinases 30,35,50 . Because this tyrosine phosphorylation induces an intramolecular interaction in Band 3, which causes dissociation of the spectrin‐actin cortical cytoskeleton from the membrane, 34,35 we hypothesised that oxidative stress deriving from premature HbS denaturation 25,28,29 might initiate a phosphorylation cascade, which would lead to dissociation of the spectrin‐based cytoskeleton from the membrane, causing membrane destabilisation and fragmentation. To test this hypothesis, we compared tyrosine phosphorylation of Band 3 in sickle cells and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the RBC lifetime, these circulating cells are exposed to a variety of internal and external oxidative stresses, despite the presence of antioxidant systems that maintain Hb in the reduced functional form 5 . Hb autoxidation and impaired antioxidant capacity favor a pro-oxidative milieu in sickle RBCs compromising the redox state of RBCs and impairing metabolic processes 6 8 . For instance, ferrous (Fe 2+ ) HbS autoxidizes to the non-functional ferric (Fe 3+ ) (metHb) species faster than normal Hb (HbA), despite the presence of reducing enzymes, causing metHb accumulation inside the RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…En el SD la elevada producción de ERO y ERN, es causada por diversos mecanismos; tales como: niveles excesivos de hemoglobina libre con acción catalítica sobre las reacciones oxidativas; daño recurrente por la isquemia-reperfusión; estado proinflamatorio crónico y alta oxidación de la HbS (8)(9)(10)15,(22)(23), lo que puede ocasionar un efecto negativo sobre proteínas, lípidos y ácidos nucleicos. Los eritrocitos de los pacientes suelen exhibir peroxidación lipídica y oxidación de grupos tiólicos.…”
Section: Introductionunclassified